Demineralization of eucalyptus biochar with hydrochloric acid: A kinetic study - VITORIA S. SILVEIRA; LUCIO ROSSO NETO; CARLOS HENRIQUE BORGERT; TIAGO ELIAS A. FRIZON; DANÚBIA J. CUZZUOL; SUMBAL SABA; MATHEUS VINICIUS GREGORY ZIMMERMANN; EDUARDO JUNCA (Anais da Academia Brasileira de Ciências)
Abstract One of the alternatives for reducing carbon emissions in the steel industry is the use of bio-coals. However, the use of biomass and its derivatives in steelmaking processes presents technical challenges due to their different chemical and physical characteristics to fossil fuels. In this context, this study aims to evaluate the effect of hydrochloric acid on the demineralization of eucalyptus charcoal, in order to understand its properties and potential application in the steel industry. To this end, the charcoal was subjected to a demineralization process using hydrochloric acid, varying the liquid-solid ratio (10:1 – 20:1) and molar concentration (1 - 3 M). The samples were then filtered, washed with deionized water and dried in an oven. The biochar was then characterized by determining surface area, moisture content, volatile content, ash content, fixed carbon content and kinetic analysis. The results showed that the surface area of the treated biocarbons increased by up to 438.38%, there was a reduction in the ash content of up to 91% and the activation energy of the gasification reaction varied between 54.8 and 109.9 kJ/mol.